Hybrid Cryptosystem dengan Algoritma 3DES dan AES dalam Pengamanan File Text - Simanjuntak, Vlen; Silalahi, David Kristian; Pasaribu, Yulanda Pasaribu (LPPM-ITEBA, 2025)
This research aims to improve the security of text data by implementing a hybrid cryptosystem that combines the 3DES and AES algorithms, both of which are symmetric cryptographic algorithms that have proven to be effective. This research utilizes the Python programming language and cryptography library to implement the algorithm with CBC mode of operation and PKCS7 padding. The encryption process begins by randomly generating a symmetric key for each session, which is then encrypted using the recipient's public key. The 3DES algorithm is implemented to provide additional protection through three rounds of encryption, while AES is used for efficiency and speed in data processing. In the decryption stage, the recipient uses the private key to unlock the encrypted symmetric key, and then uses the key to decrypt the encrypted data. The results obtained show that the combination of these two algorithms increases resistance to attacks such as brute force and chosen plaintext, providing an optimal balance between efficiency and security in securing text data. With these results, the hybrid cryptosystem approach can be applied in various applications that require text data protection, offering a robust and reliable security solution in the secure exchange of information.